THE RELATIONSHIP BETWEEN LIQUIDITY AND PROFITABILITY: AN EMPIRICAL STUDY FOR THE CASE OF ALKALOID - Angela Zafirova (Journal of International Balkan University-Faculty of Economics and Administrative Sciences, 2020)
The relationship between liquidity and profitability is one of the most popular topics of research in the financial management field but still not exhaustively examined and documented for the industries in the Republic of North Macedonia. Taking into account the importance of the pharmaceutical industry for every country’s well-being, the purpose of this paper is to examine the relationship between liquidity and profitability in the pharmaceutical sector in the Republic of North Macedonia. This paper analyzes the biggest and the most influential pharmaceutical producer and seller in the RNM, listed on the Macedonian Stock Exchange. For its purpose, this empirical research has used secondary annual financial data over the period 2010 – 2019. Current ratio (CR), quick ratio (QR) and cash ratio (CAR) were used to measure the liquidity position while return on assets (ROA) and return on equity (ROE) were used to measure the company’s profitability. The statistical tests performed, primarily involved were descriptive statistics, correlation and regression analysis. The findings suggest that there is negative relationship between profitability and liquidity determinants of the biggest North Macedonian pharmaceutical firm. This study contributes to the existing literature in this field and represents one of the pioneer attempts in the case of RNM.